P=2
Work:
<span><span><span>7p</span>−<span>(<span><span>3p</span>+4</span>)</span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span>7p</span>−<span>(<span><span>3p</span>+4</span>)</span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span>7p</span>+<span><span>−1</span><span>(<span><span>3p</span>+4</span>)</span></span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span>7p</span>+<span><span>−1</span><span>(<span>3p</span>)</span></span></span>+<span><span>(<span>−1</span>)</span><span>(4)</span></span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span><span><span>(<span>−2</span>)</span><span>(<span>2p</span>)</span></span>+<span><span>(<span>−2</span>)</span><span>(<span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span><span>−<span>4p</span></span>+2</span>+10</span></span><span><span><span>(<span><span>7p</span>+<span>−<span>3p</span></span></span>)</span>+<span>(<span>−4</span>)</span></span>=<span><span>(<span>−<span>4p</span></span>)</span>+<span>(<span>2+10</span>)</span></span></span><span><span><span>4p</span>+<span>−4</span></span>=<span><span>−<span>4p</span></span>+12</span></span><span><span><span>4p</span>−4</span>=<span><span>−<span>4p</span></span>+12</span></span><span><span><span><span>4p</span>−4</span>+<span>4p</span></span>=<span><span><span>−<span>4p</span></span>+12</span>+<span>4p</span></span></span><span><span><span>8p</span>−4</span>=12</span><span><span><span><span>8p</span>−4</span>+4</span>=<span>12+4</span></span><span><span>8p</span>=16</span><span><span><span><span><span>8p</span>8</span></span></span>=<span><span><span>168</span></span></span></span><span>p=<span>2
Hope this helps:)</span></span>
Answer:
I can help you but first I need the rest of the answers to find out what's it equivalent to.
Answer:
0.345 is greater than 0.333
Step-by-step explanation:
If you go down the line of numbers the first two numbers match but then you get a 4 and 3. 4 is greater then 3 so 0.345 is greater than 0.333
Answer:
The answer is D.) x-3
Step-by-step explanation:
Answer:
![c =\frac{8}{3}](https://tex.z-dn.net/?f=c%20%3D%5Cfrac%7B8%7D%7B3%7D)
Step-by-step explanation:
Given
![c = \sqrt{\frac{4 + \sqrt 7}{4 - \sqrt 7}} + \sqrt{\frac{4 - \sqrt 7}{4 + \sqrt 7}}](https://tex.z-dn.net/?f=c%20%3D%20%5Csqrt%7B%5Cfrac%7B4%20%2B%20%5Csqrt%207%7D%7B4%20-%20%5Csqrt%207%7D%7D%20%2B%20%20%5Csqrt%7B%5Cfrac%7B4%20-%20%5Csqrt%207%7D%7B4%20%2B%20%5Csqrt%207%7D%7D)
Required
Shorten
We have:
![c = \sqrt{\frac{4 + \sqrt 7}{4 - \sqrt 7}} + \sqrt{\frac{4 - \sqrt 7}{4 + \sqrt 7}}](https://tex.z-dn.net/?f=c%20%3D%20%5Csqrt%7B%5Cfrac%7B4%20%2B%20%5Csqrt%207%7D%7B4%20-%20%5Csqrt%207%7D%7D%20%2B%20%20%5Csqrt%7B%5Cfrac%7B4%20-%20%5Csqrt%207%7D%7B4%20%2B%20%5Csqrt%207%7D%7D)
Rationalize
![c = \sqrt{\frac{4 + \sqrt 7}{4 - \sqrt 7} * \frac{4 + \sqrt 7}{4 + \sqrt 7}} + \sqrt{\frac{4 - \sqrt 7}{4 + \sqrt 7}*\frac{4 - \sqrt 7}{4 - \sqrt 7}}](https://tex.z-dn.net/?f=c%20%3D%20%5Csqrt%7B%5Cfrac%7B4%20%2B%20%5Csqrt%207%7D%7B4%20-%20%5Csqrt%207%7D%20%2A%20%5Cfrac%7B4%20%2B%20%5Csqrt%207%7D%7B4%20%2B%20%5Csqrt%207%7D%7D%20%2B%20%20%5Csqrt%7B%5Cfrac%7B4%20-%20%5Csqrt%207%7D%7B4%20%2B%20%5Csqrt%207%7D%2A%5Cfrac%7B4%20-%20%5Csqrt%207%7D%7B4%20-%20%5Csqrt%207%7D%7D)
Expand
![c = \sqrt{\frac{(4 + \sqrt 7)^2}{4^2 - (\sqrt 7)^2}} + \sqrt{\frac{(4 - \sqrt 7)^2}{4^2 - (\sqrt 7)^2}](https://tex.z-dn.net/?f=c%20%3D%20%5Csqrt%7B%5Cfrac%7B%284%20%2B%20%5Csqrt%207%29%5E2%7D%7B4%5E2%20-%20%28%5Csqrt%207%29%5E2%7D%7D%20%2B%20%20%5Csqrt%7B%5Cfrac%7B%284%20-%20%5Csqrt%207%29%5E2%7D%7B4%5E2%20-%20%28%5Csqrt%207%29%5E2%7D)
![c = \sqrt{\frac{(4 + \sqrt 7)^2}{16 - 7}} + \sqrt{\frac{(4 - \sqrt 7)^2}{16 - 7}](https://tex.z-dn.net/?f=c%20%3D%20%5Csqrt%7B%5Cfrac%7B%284%20%2B%20%5Csqrt%207%29%5E2%7D%7B16%20-%207%7D%7D%20%2B%20%20%5Csqrt%7B%5Cfrac%7B%284%20-%20%5Csqrt%207%29%5E2%7D%7B16%20-%207%7D)
![c = \sqrt{\frac{(4 + \sqrt 7)^2}{9}} + \sqrt{\frac{(4 - \sqrt 7)^2}{9}](https://tex.z-dn.net/?f=c%20%3D%20%5Csqrt%7B%5Cfrac%7B%284%20%2B%20%5Csqrt%207%29%5E2%7D%7B9%7D%7D%20%2B%20%20%5Csqrt%7B%5Cfrac%7B%284%20-%20%5Csqrt%207%29%5E2%7D%7B9%7D)
Take positive square roots
Take LCM
![c =\frac{4 + \sqrt 7 + 4 - \sqrt 7}{3}](https://tex.z-dn.net/?f=c%20%3D%5Cfrac%7B4%20%2B%20%5Csqrt%207%20%2B%204%20-%20%5Csqrt%207%7D%7B3%7D)
Collect like terms
![c =\frac{4 + 4+ \sqrt 7 - \sqrt 7}{3}](https://tex.z-dn.net/?f=c%20%3D%5Cfrac%7B4%20%20%2B%204%2B%20%5Csqrt%207%20-%20%5Csqrt%207%7D%7B3%7D)
![c =\frac{8}{3}](https://tex.z-dn.net/?f=c%20%3D%5Cfrac%7B8%7D%7B3%7D)